International Webinar Cultural Diversity Indonesian and Philippine - *Lili Nurlaili; Ichwani Siti Utami; Hendri Hendri (Universitas Syiah Kuala, 2022)
The development of globalization has a significant impact on changes in various aspects of the lives of Indonesian people today and even throughout the world. One of the effects of globalization is that it provides convenience in accessing all information in the world, both about culture, education, politics and others. Therefore, in following up on the collaboration between the University of Pamulang (UNPAM) and the Polytechnic University of the Philippines (PUP), which is followed by the collaboration of the Faculty of Teacher Training and Education, the PPKn Study Program will hold a web seminar (webar) on culture, educational policies and the democratic system that growing in Indonesia and the Philippines. This activity is carried out in a video conference platform (webinar). This international community service (PKM) aims to: a) Increase knowledge about Cultural Diversity in Indonesia and the Philippines; b) Improve the ability to understand about Cultural Diversity in Indonesia and the Philippines; c) Raising awareness of the importance of understanding medium-sized Cultural Diversity in Indonesia and the Philippines; d) Instilling concern for Cultural Diversity in Indonesia and the Philippines; e) Improve the ability to implement understanding of Cultural Diversity in their respective environments; f) Instilling awareness about the Cultural Diversity learning model in Indonesia and the Philippines.